Methodological Rationale for the Taxonomy of the PO.EX Digital Archive - Torres, Rui (2018)
The PO.EX Digital Archive aims to create a digital representation of large corpus of intermedia literary works produced by Portuguese authors since the 1960s. In the process of remediating these works for the current digital networked environment we address metadata issues in a way that satisfies both our material and textual analysis of intermediality, and also the interoperability requirements of current information systems. The creation of a taxonomy for organizing and classifying a diverse array of materials such as those that constitute the digital archive of Portuguese Experimental Poetry (which includes Performance, Digital, Concrete, Spatial, Sound, Video, and Visual poetry) is a challenging task for the present researchers. The purpose of this article is to offer a brief rationale for our decisions, and to explain and illustrate our classification system.